Identification of Suitable Sites for Rainwater Harvesting Using AHP and GIS in the Middle and High Moulouya Basin, Morocco - Amiri Mustapha; Bouguelba Smail; Sbai Abdelkader; Ghzal Mohamed; Qadem Zohair; Salem Ali (E3S Web of Conferences)
Several researchers have utilized various methodological frameworks to determine appropriate locations and methodologies for Runoff Water Harvesting (RWH) in semi-arid and arid area. This plays a crucial role in addressing water scarcity during dry periods. Establishing RWH sites within basins to collect rainwater from small basin and facilitate artificial groundwater replenishment is a viable solution to mitigate water deficiencies in the middle and upper Moulouya basin. In this study, a methodology integrating remote sensing data and geographic information systems was developed based on a model created in SIG software. Seven factors including lithology, climate, land cover/land use, digital elevation, recharge, and surface runoff. Were employed to assess the suitability of sites for RWH. The resulting spatial distribution of the suitability map categorized the basin into five classes of RWH potential, ranging from very high to very low suitability. These findings offer significant promise in terms of identifying suitable sites for RWH. The RWH suitability map revealed that within the Moulouya basin, areas were classified into unsuitable (20.15%), less suitable (40.82%), moderately suitable (24.38%), well-suited (9.60%), and highly suitable (5.02%) categories for RWH. This final map serves as a valuable resource for decision-makers, hydrologists, and urban planners, offering crucial guidance for future water resource and land management initiatives by swiftly pinpointing areas with the highest potential for rainwater harvesting.